Language Vitality among Acehnese Parents and Its implication to Language Maintenance: On Perspective of Expanded Graded Intergenerational Disruption Scale (EGIDS) - Idaryani Idaryani; Fidyati Fidyati (Journal of English Language and Education, 2022)
Research on the vitality of  Acehnese language is very important among the dominance use of Bahasa Indonesia among Acehnese.  Even, UNESCO recently has paid more attention to the world's languages and make efforts to revitalize potentially extinct languages. Acehnese as one of the heritage languages in Aceh Province, Indonesia also faces risk of extinction due to the shirnk of its domain usage. The purpose of this research is to investigate language vitality among Acehnese female parents in Lhokseumawe city. Qualitative approach was carried out in this study by conducting semi-structured observations, interviews, and strengthened with questionnares delivered to the participants by adopting  questionaire model proposed by Cohn (2013). The result of the study shows that vitality of Acehnese language among parents is still strong as a means of communication among certain people and in certain public domains such as in traditional market and around their neigbourhood.  Parents also still use Acehnese in family domain with their spouse, and their neighbourhood, however, the vitality of Acehese among parents becomes problematic because most of the parents do not longer use Acehnese when communicating to their children at home on their daily basis.